In-depth study of homogeneity in DBS using two different techniques: results from the EBF DBS-microsampling consortium. (September 2013) - Cobb, Zoe; de Vries, Ronald; Spooner, Neil; Williams, Stephen; Staelens, Ludovicus; Doig, Mira; Broadhurst, Rebecca; Barfield, Matthew; van de Merbel, Nico; Schmid, Bernhard; Siethoff, Christoph; Ortiz, Jordi; et al.
Background: At the start of their work, the European Bioanalysis Forum dried blood spots microsampling consortium did not form a dedicated team to investigate the spot homogeneity. However, two teams performed experiments that produced results relating to sample homogeneity.Results: The data, which were produced via two different approaches (a radiolabeled and a nonradiolabeled approach), are highly complementary and demonstrate clear effects on sample inhomogeneity due to the substrate type, compound and hematocrit levels.Conclusion: The results demonstrate that sample inhomogeneity is a significant hurdle to the use of dried blood spots for regulated bioanalysis that should be investigated further in the method establishment phase if the whole spot is not sampled.